A Novel Estimation Approach of Unconfined Compressive Strength (UCS) and Improved Rock Mechanical Properties Correlations by Considering The Effect of Overpressure Condition, Mineralogy, and Shale Composition in Montney Shale Gas, British Columbia, Canada - Savitri, C.D. (American Rock Mechanics Association (ARMA), 2021)
Various studies have been done to develop dynamic rock mechanical properties (RMP) and rock strength of shale gas to estimate high accuracy value prediction when no core is available. However, previous studies did not consider the overpressure, mineralogy, and shale composition in their correlations. This study aims to improve dynamic rock mechanical properties and develop an Unconfined Compressive Strength (UCS) estimation from sonic transit time data by considering the overpressure, mineralogy and shale composition. The data of this research are gathered from British Columbia Oil and Gas Commission (BCOGC). In this study, firstly, the pore pressure is predicted and the result shows that the Montney formation could be divided into Upper Montney and Lower Montney. Secondly, the static and dynamic rock mechanical properties are correlated by using Adaptive Neuro Fuzzy Inference System (ANFIS) according to the pore pressure zone. Thirdly, the novel UCS estimation is developed, and the finding presented an agreeable result with the field validation. This study is expected to provide more accurate and rigorous rock mechanical properties and rock strength estimation which leads to better prognosis in operational strategies and hydraulic fracturing location planning in shale gas development when geomechanical analysis needs to be addressed when no core is available. Copyright Â© 2021 ARMA, American Rock Mechanics Association.